Powershift: Knowledge, Wealth, and Violence at the Edge of the 21st Century - Alvin Toffler (Bantam Books, 1990)
Discusses power at the edge of the 21st century. Deals with violence, wealth and knowledge and the roles they play in our lives; and discusses new paths to power opened by a world of upheaval.